Midterm outcomes of total hip arthroplasty with a modular Birmingham head. Issue 1 (January 2021) - Cushnie, Duncan W; Lanting, Brent A; McCalden, Richard; Naudie, Douglas DR; Howard, James L
Introduction: Birmingham Hip Resurfacing (BHR) implants may be combined with a conventional femoral stem to create a modular metal-on-metal total hip arthroplasty (BHR MoM THA). There is little outcome data regarding this construct. This study examines midterm outcomes of BHR MoM THA compared to oxidised zirconium total hip arthroplasty (THA). Methods: A retrospective institutional review identified all patients receiving BHR MoM THA between April 2005 and February 2011 and a matched control cohort of zirconium THA patients. Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Harris Hip Score (HHS), and SF-12 Health status scores were obtained. Revisions and complications were collected from clinical records. Radiographs were assessed for evidence of component malposition, loosening, osteolysis, or heterotopic ossification. Results: 63 modular BHR MoM THA were identified in 61 patients (36 with BHR cups, 27 with R3 cups) and 63 zirconium THA in 58 matched controls. Mean follow-up was 58 months. 14 BHR MoM THA hips (22.2%) were revised (4 infections, 1 dislocation, 9 soft tissue reactions) compared to 3 (4.8%) zirconium THA (all infections). At latest follow-up, 18.4% of surviving BHR MoM THA hips were painful compared to 0.5% of zirconium THA controls ( p < 0.001). WOMAC, HHS, and SF-12 did not differ significantly between surviving members of the 2 groups. Discussion: BHR MoM THA demonstrated a high revision rate, largely for adverse local soft tissue reaction and pain. Among those not revised, many reported some residual pain despite similar quality of life measures to those who received zirconium THA.